Abdul – Lateef Aqel As Apoet - Muaath Abullah Ishtaey (My University, 2003)
In this study, I tried to recognize the poetic character of Abdu-Latif Aqel through his works. I investigated the most prominent issues related to his poetic production. However, this does not mean that I have given the final word about the poet’s character and his creativity since the investigation of the poetic character of Aqel needs research of literary production related to three decades of the history of the Palestinian cause. Findings Among the most prominent findings that I have reached through my study of the poetic experience of the poet are the following: -The suffering that Abdul-Latif Aqel experienced at the personal level had an impact upon forming his poetic character and crystallizing his creativity. He led a life that lacked balance after losing his father and sister and the fact that his mother got married. -Deprivation of the woman seemed to be a major cause of her possession of the poet’s feelings during the early productions of his poetic experience. The image of the woman in his early poems seemed to comprise a part of his poetic readings. -The poet experienced the sufferings of his nation that included banishment, Judaization, expulsion, eviction, torturing, land confiscation, colonization, discrimination, and ignorance policies. All of those measures had a great impact on fostering his resistance attitude. -The poet took the commitment path in most of his poetic production as he realized the role of the word in the struggle movement. He implemented his talents and artistic abilities to defend the cause of his people. In his poetry, he discussed the political worries, the issues, and all the events of his homeland, expressing his love for his land, and calling for steadfastness in it. -The poet took great care in representing the Palestinian in various types as a refugee, a prisoner, and a martyr. These types seemed to reflect one side or another of the homeland embodying its hopes and pains. -The poet unveiled the misleading deceptive image of the occupation. Not only was he able to express the Palestinian refusal of the occupation, but he also urged the Palestinians to resist it. He seemed to believe that the revolution is the way of salvation. He expressed his enthusiasm towards the revolution and declared his yearning for the coming revolutionist.In his poetry, he portrayed a negative image of the Arab reality as a result of the defeatist political stands that some of the formal Arab regimes adopted regarding the Palestinian cause. -The poet depended on various poetic forms in constructing his artistic structure which included the following forms: the traditional poem, the metric poem, the long poem, and then back to the traditional poem. -The poet seemed to realize the important role of the language in the artistic work. Therefore, his linguistic lexicon reflected not only the resistance spirit in himself, but it was also in harmony with the reality that he expressed and the nationalistic soul that interacted inside himself. He implemented some linguistic phenomena such as repetition and symbolism in constructing his poems. -The poet exploited various linguistic styles in constructing his poems. He was influenced by the dramatic construction and employed some of them such as quotation, sarcasm, interrogation, and vocative. -The poet was especially interested in the image which he formed from vocabulary that had Palestinian characteristic. In his poetry, he employed various styles in constructing his individual and compound images including personification, abstraction, and embodiment in building a lot of his individual images. He employed the dramatic and syllabic construction in forming his compound images. -The external music in his poetry was in harmony with the music of modern poetry. Al-Ramal metre occupied the first rank in his poetry. -The poet depended on various linguistic phenomena in forming his internal music including repetition of letters, words, and phrases.

حاولت في هذه الدراسة أن أقف على شخصية عبد اللطيف عقل الشعرية من خلال أعماله، وقد حرصت على البحث في أبرز القضايا التي تتصل بنتاجه الشعري، ولكنّ ذلك لا يعني أنني قلت الكلمة الأخيرة في شخصية الشاعر وإبداعه، إذ إن البحث في شخصية عقل الشعرية هو دراسة لنتاج أدبي يتصل بثلاثة عقودٍ من تاريخ القضية الفلسطينية. ومن أبرز النتائج التي توصلت إليها في دراستي لتجربة الشاعر الشعرية، ما يلي: ·كان للمعاناة التي عاشها عبد اللطيف عقل على المستوى الشخصي أثر في تشكيل شخصيته الشعرية وبلورة إبداعه، فقد عاش حياة تفتقر إلى التوازن بعد أن فقد والده وأخته وتزوجت أمه. ·بدا الحرمان من المرأة سبباً رئيساً في هيمنتها على وجدان الشاعر في البواكير الأولى لتجربته الشعرية، وقد بدت صورتها في قصائده الأولى جزءاً من مقروء الشاعر الشعري. ·عاش الشاعر معاناة شعبه من تشريد وتهويد ونفي وتهجير وتعذيب وتنكيل ومصادرة أراضٍ وبناء مستوطنات، وسياسة تجهيل واستلاب فكر وتمييز، وقد كان لذلك أثرٌ في بروز الاتجاه المقاوم لديه. ·سلك الشاعر طريق الالتزام في معظم نتاجه الشعري، حيث وعى دور الكلمة في الحركة النضالية وراح يسخّر موهبته وقدراته الفنية في سبيل الدفاع عن قضية شعبه، وقد تناول في شعره الوطن بهمومه السياسية وقضاياه وأحداثه كافة، وعبّر عن حبه لأرضه، ودعا إلى الصمود فيها. ·حرص الشاعر على تقديم صورة الفلسطيني من خلال نماذج متعددة تتمثل في شخصية اللاجئ والسجين والشهيد، وقد بدت هذه النماذج تعكس في حضورها وجهاً من وجوه الوطن وتجسد آماله وآلامه. ·كشف عن الصورة الخادعة والمضللة للمحتل، واستطاع فوق ذلك كله أن يعبّر عن رفض الفلسطيني للاحتلال وأن يدعو إلى مقاومته، وقد بدا يؤمن بالثورة حلاً للخلاص حين بث تفاؤله بها، وأعلن شوقه للثائر القادم. ·رسم في شعره صورة سلبية للواقع العربي وقد تغذى مضمونها على المواقف السياسية المتخاذلة التي تبنتها بعض الأنظمة الرسمية العربية تجاه القضية الفلسطينية. ·اعتمد الشاعر على أشكال شعرية متعددة في صياغة بنائه الفني، وقد سارت بنية القصيدة في شعره على النحو التالي: القصيدة العمودية، قصيدة التفعيلة، المطولة الشعرية، ثم العودة إلى القصيدة العمودية. ·بدا الشاعر مدركاً للدّّور المهم الذي تؤديه اللّغة في العمل الفني، من هنا، جاء معجمه اللّغوي يعكس الروح المقاومة في نفسه، وينسجم مع الواقع الذي يعبّر عنه، وينسجم مع الروح الوطنية التي تتفاعل في نفسه، وقد وظف بعض الظواهر اللغوية في تشكيل قصائده مثل التكرار والرمز. ·اعتمد الشاعر على غير أسلوب من الأساليب اللغوية في بناء قصائده، فقد تأثر بأساليب البناء المسرحي ووظّف بعضاً من التقنيات الفنية، كالاقتباس والسخرية والاستفهام والنداء. ·حظيت الصورة بعناية الشاعر الخاصة فقد شكلها من مفردات ذات خصوصية فلسطينية، وعمد في أشعاره إلى توظيف وسائل تصويرية مختلفة في بناء صوره المفردة والمركبة، حيث استخدم التشخيص والتجسيم والتجريد في بناء كثيرٍ من صوره المفردة، ووظف البناء الدرامي والمقطعي في تشكيل صوره المركبة. ·جاءت الموسيقى الخارجية في شعر عقل منسجمة مع موسيقى الشعر الحديث، حيث حظيت تفعيلة الرمل بالمرتبة الأولى في شعره. ·اعتمد الشاعر على ظواهر لغوية متنوعة في تشكيل موسيقاه الداخلية أبرزها تكرار الحروف وتكرار الألفاظ وتكرار العبارات.
عبد اللطيف عقل شاعرا